FEATURES OF THE DEVELOPMENT OF REGIONAL POULTRY PRODUCTS MARKETS - HRYVKIVSKA, Oksana; KRASNORUTSKYY, Oleksiy (Herald of Khmelnytskyi National University. Economic sciences, 2023)
One of the most efficient branches of the agro-industrial complex is the poultry industry, which provides the highest yield per unit of spent material and technical resources. The poultry industry is characterized by the absence of seasonality in production, which ensures uniform income and use of labor resources, as well as uninterrupted supply of products to the population. The most important factor in the development of the industry is the existence of a balanced market. In the conditions of significant import dependence that remains, improving the formation of the domestic market for poultry products is one of the urgent tasks of science and practice, the solution of which will allow to saturate the market with dietary and high-quality food products. The article substantiates the factors of the rapid growth of production of poultry products: the lowest costs compared to other types of livestock for obtaining an increase of 1 kg of live weight; activation of investment investments; technical and technological renewal of the material base and expansion of production capacities; quality improvement of genetic material; use of modern marketing tools; state of supply and demand; competitive environment; favorable characteristics of the geographical, natural-climatic and demographic aspects of the placement of regional markets; Orientation when placing poultry enterprises on vertical integration, including proximity to the fodder base; state financial support of the industry. The production of poultry meat during 2000-2023 and chicken eggs was analyzed. A detailed review of the supply of poultry products on the markets and the reasons for its change during 2021-2023 was conducted. The state and prospects for the development of export-import operations on regional poultry markets and Ukraine's participation in these processes are disclosed. It is well-founded that future success is determined by planning all business processes not for the long term; the existence/absence of grain agreements at the international level; the conjuncture of similar foreign goods and world prices compared to national offers; prolongation of state financial support for the industry; natural and climatic conditions of the coming years, which determine, together with the innovation and investment renewal of enterprises in the industry, the prospects for feed prices, production volumes, product prices and consumer demand volumes.
Keywords: poultry farming; poultry products; food; poultry meat; production; regional markets of poultry products